Trabalho e Ciência: Um olhar para a saúde e qualidade de vida dos professores universitários - Cancian, Queli Ghilardi (2020)
It has been known that work influences over the perception of life qualify and health condition of human beings. The professors, during the exercise of their duties, are exposed to innumerous factors that may interfere directly over their life quality, letting them vulnerable to the spring of mental illnesses. Before the several changes throughout teaching organization, we present the aim of this research herein as both identification and analysis of the perception that professors from Federal University of Oeste do Paraná – UNIOESTE (Campus Cascavel / PR) have with respect to their own mental health and life quality. This is about quali-quanti research, with an exploratory feature, descriptive design and comparative approach. In order to develop this research, we performed a bibliographic review aiming at the building of a theoretical referential. For the verification of the hypothesis, we also performed a field research. Data collection was based on questionnaires developed by the researchers. The first questionnaire was addressed to professors; the second one to professors that play administrative roles like Campus Manager, Center Managers and Course Coordinators. For the statistical analysis of data, we opted by SPSS 22.0 program (Portuguese version). The analysis suggested the excessive workload are a result from the multi functions attributed to these professionals related to teaching, researching and extension, which has contributed to diminution of their life quality and mental health. Data also pointed that, according to their perception, the main mental health problems are anxiety and stress, or stress and anxiety, in the case of the managers mentioned above. Life quality is assessed from four main domains: (1) physical or (2) metal health; and (3) workplace or (4) social relations. Results showed that social relations, as well as workplace ones, influence over mental health in both positive and negative aspects, however, such factors allied to an excessive workload contribute to an increase of mental illnesses related to workplace.